Point of Care Technology: A Sociotechnical Approach to Home Health Implementation - Stricklin, M. L. V.; Struk, C. M. (Methods of Information in Medicine, 2003)
Objectives: This paper describes an ongoing evaluation study of the design and implementation of Point of Care (POC) technology in a home health agency. Methods: During the implementation of POC technology data about user acceptance were collected with the help of surveys and statistically analyzed. The survey also allowed for entering non-structured observations. A time series study was conducted to identify factors associated with technology change and its effect on professional competency.Results and Conclusions: Healthcare markets and consumers are demanding that providers use sophisticated information technology to document, transmit and access clinical and financial information across all delivery points. Newly adapted Patient Care Information Systems (PCIS) are available for clinical use in home care. The factors associated with home care nurses’ end user acceptance and use of the POC technology in clinical work are described. A sociotechnical approach with selected change management strategies appears to have positively influenced the nurse end users’ POC technology adoption and use in clinical work.
Keywords: Healthcare informatics; point of care technology; change management; home healthcare; sociotechnical approach; patient care information systems; nursing information systems